The Influence Attribute Product to Loyalty Consumer Through Satisfaction Consumer as Intervening Variables (Case Study on Players Games Online Valorant in Surabaya City) - Raihan Hafifi; Nurul Azizah (International Journal of Economics (IJEC), 2024)
Various new games have emerged with the changing times. Riot Games is a video game development company that has successfully produced a First Person Shooter (FPS) game named “ Valorant ”. Despite being relatively new, this game has managed to capture the interest of FPS enthusiasts. This study aims to determine how the effect of product attributes consisting of product quality, product features, and product style and design through customer satisfaction as an intervening variable on Valorant consumer loyalty in Surabaya. The method used in this research is a quantitative method with a descriptive approach. This study uses purposive sampling technique with population provisions including 17 years and over, domicile in Surabaya City, and playing and purchasing virtual products in Valorant since the last 2 years, so that a sample of 100 respondents was obtained. The data collection used a questionnaire distributed online. The data analysis method uses path analysis and is processed using Statistical Program for Social Science (SPSS) software. The results obtained in this study indicate that the influence of product quality variables, product features, and product style and design each have a significant influence on consumer loyalty. Variable Customer satisfaction has a significant effect on customer loyalty. The product quality variable does not have a significant effect on consumer loyalty. The variables of product features and product style and design each have a significant influence on consumer loyalty.